Royal tourists, colonial subjects and the making of a British world, 1860-1911 - Reed, Charles V. (Studies in imperialism (Manchester, England), 2017)
Royal Tourists, Colonial Subjects and the Making of a British World, 1860-1911 examines the ritual space of nineteenth-century royal tours of empire and the diverse array of historical actors who participated in them. The book suggests that the varied responses to the royal tours of the nineteenth century demonstrate how a multi-centred British imperial culture was forged in the empire and was constantly made and remade, appropriated and contested. In this context, subjects of empire provincialised the British Isles, centring the colonies in their political and cultural constructions of empire, Britishness, citizenship and loyalty.